Life in the suburbs after "Grootboom": the role of local government in realising housing rights in the Eastern Cape - Kruuse, Helen Julia (Rhodes University, Faculty of Law, Law, 2008)
When the Government of National Unity took office in 1994, it inherited a country with severe inequalities in resource distribution and land ownership. In particular, it inherited a housing crisis which was, to a large extent, caused by apartheid legislation and policies. This research focuses on the housing crisis post-1994 by considering the impact and effect of the constitutional right to have access to adequate housing, especially for those living in intolerable conditions. It does so by utilising a social-scientific approach to the law. This approach acknowledges that the housing right must exist alongside other social phenomena and as a part of everyday life in South Africa. Accordingly, the implementation of the housing right by three local municipalities in the Eastern Cape is examined. Following an initial overview of the history of housing and local government in South Africa, the study focuses on the current legislative framework for housing and theinterpretation of the housing right (and other socio-economic rights) in certain court decisions. These decisions are discussed, not only because of the impact they have had on communities living in intolerable situations, but, as importantly, because they have developed standards against which policy and planning should be measured. These standards are used in the study to evaluate housing provision in three municipalities. The evaluation (by means of interviews and assessment of planning documentation) demonstrates that the recognition of the housing right in the Constitution and by the courts does not necessarily translate into effective recognition and implementation by the state. The research shows that the failure to plan proactively, lack of co-operative governance and inadequate controls over financial and human resources thwart the realisation of the housing right by local government. It is recommended that, in order to make the housing right a reality, research into the housing right (and indeed other socio-economic rights) should scrutinise the management of financial and human resources of the state in the context of the policy, planning and implementation environment. Where research is able to show evidence of unspent budgets, insufficient planning and mismanagement of resources, courts would be able to focus on the implementation aspect of the housing right, and ensure that it may yet have a meaningful impact on the lives of millions of some of the most vulnerable people in society.
Keywords: Right to housing; Human rights -- South Africa -- Eastern Cape; Local government -- South Africa -- Eastern Cape; Housing -- Law and legislation -- South Africa -- Eastern Cape; Housing policy -- South Africa -- Eastern Cape; Low income housing -- South Africa -- Eastern Cape